Obstructive membrane in arch of aorta in a case of Shone's complex - Sadadiwala, Divyesh H. (Ann Card Anaesth, 2015)
Shone's complex is a rare congenital heart disease consisting of multisite obstruction on the left side of the heart. The obstructive membrane in the arch of aorta is never described among these obstructions. We report echocardiographic findings in a patient with Shone's complex with the obstructive membrane in the arch of aorta.